2009
DOI: 10.1002/jps.21525
|View full text |Cite
|
Sign up to set email alerts
|

Biowaiver Monographs for Immediate Release Solid Oral Dosage Forms: Diclofenac Sodium and Diclofenac Potassium

Abstract: Literature data are reviewed regarding the scientific advisability of allowing a waiver of in vivo bioequivalence (BE) testing for the approval of immediate release (IR) solid oral dosage forms containing either diclofenac potassium and diclofenac sodium. Within the biopharmaceutics classification system (BCS), diclofenac potassium and diclofenac sodium are each BCS class II active pharmaceutical ingredients (APIs). However, a biowaiver can be recommended for IR drug products of each salt form, due to their th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 50 publications
(41 reference statements)
4
84
1
9
Order By: Relevance
“…Diclofenac is a non-steroidal anti-inflammatory drug with analgesic, anti-inflammatory and antipyretic properties, was chosen as the model compound [5]. It is reported that absorption of diclofenac occurs throughout the intestinal tract [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diclofenac is a non-steroidal anti-inflammatory drug with analgesic, anti-inflammatory and antipyretic properties, was chosen as the model compound [5]. It is reported that absorption of diclofenac occurs throughout the intestinal tract [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diclofenac potassium is claimed to dissolve faster and hence absorbed faster, than the sodium salt and is recommended for the treatments that need short onset of action, mainly for its analgesic properties 21 . Although there were differences between IC 50 values of sodium and potassium salts of diclofenac, a statistical evaluation was not performed (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Since DS has pH dependent solubility such as 0.14 mg DS is soluble in 1 mL of pH 5.8 phosphate buffer and 5.15 mg DS soluble in 1 mL pH 7.4 phosphate buffer at 23±2°C, 29 a pH value which DS is less soluble in the external phase was selected in order to increase encapsulation efficiency. 22 Lowering the external pH from 7.4 to 5.8 (F4) resulted with an increase on encapsulated DS by 32% and from this point on all other nanoparticle formulations (F5 and F6) were prepared with pH 5.8 external phase which allows less DS escape to outer aqueous phase depending on less solubility.…”
Section: Encapsulation Efficiencymentioning
confidence: 99%